Adherence to Public Procurement Act in Tamale Polytechnic of Ghana: Rhetoric or Reality in practice? - Adusei, Charles (Archives of Business Research, 2016)
This paper examines the Public Procurement Act (PPA) 2003 (Act 663) on its adherence by Tamale Polytechnic. The key issues considered included procurement practices before and after the implementation of PPA. A well-structured questionnaire was used in collecting data from the staffs. Descriptive statistics, One Sample t-Test and Kendall’s Coefficient of Concordance were used to analyse the data. Result revealed that strict procurement procedures were not followed prior to PPA, though PPA brought sanity into the Polytechnic in their procurement processes, its implementations were bedeviled with a lot of challenges. This paper suggests that management of the Polytechnic should allow the procurement unit to operate freely without any form of interference in its quest to adhere to the PPA (Act 663).